Cutaneous Manifestations in Pediatric Autoimmune Polyendocrinopathy–Candidiasis–Ectodermal Dystrophy (APECED) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: APECED is a rare monogenic autoimmune disorder resulting from mutations in the AIRE gene. It primarily affects children and manifests with a classic triad: chronic mucocutaneous candidiasis (CMC), hypoparathyroidism, and adrenal insufficiency. Dermatological features often present early, offering a crucial opportunity for diagnosis.Objectives: This study aimed to delineate the cutaneous features in a pediatric cohort with APECED, analyze the relationship of these cutaneous manifestations with systemic disease, and assess genotype-phenotype correlation. We also explored whether ectodermal features reflect a primary dysplasia or are secondary phenomena.Methods: Twelve children diagnosed with APECED underwent multidisciplinary evaluation, including dermatologic and endocrine assessments. Detailed clinical histories, physical examinations, and genetic testing were conducted. Cutaneous features were assessed with respect to disease progression, and statistical correlation was performed to identify significant relationships.Results: All 12 children exhibited CMC, with 75% also presenting with candidal onychomycosis or paronychia. Alopecia areata occurred in 33%, while vitiligo was noted in 17%. In 17% of cases, skin findings led to early diagnosis before endocrine failure. No direct correlation was observed between AIRE mutations and skin manifestations. Statistical analysis showed that CMC and onychomycosis were significantly associated with APECED progression (p < 0.01), while vitiligo showed no significant association.Conclusions: Skin manifestations, particularly CMC and nail involvement, are highly prevalent and often precede systemic features of APECED. Recognizing these signs early can prevent life-threatening complications. The term “ectodermal dystrophy” may be misleading, as these cutaneous features likely represent secondary changes.